Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
RÚT GỌN VỀ PHÂN SỐ TỐI GIẢN
câu a) \(\dfrac{-147}{252}=\dfrac{-7}{12}\)
câu b) \(\dfrac{765}{900}=\dfrac{17}{20}\)
câu c) \(\dfrac{11\cdot3-11\cdot8}{17-6}=\dfrac{-5}{1}\)
câu d) \(\dfrac{3^5\times2^4}{8\times3^6}=\dfrac{2}{3}\)
câu e) \(\dfrac{84\cdot45}{49\cdot54}=\dfrac{10}{7}\)
\(\dfrac{-63}{72}=\dfrac{-7}{8}\)
\(\dfrac{20}{-140}=\dfrac{-1}{7}\)
\(\dfrac{3.10}{5.24}=\dfrac{30}{120}=\dfrac{1}{4}\)
\(\dfrac{3.7.11}{22.9}=\dfrac{231}{198}=\dfrac{7}{6}\)
\(\dfrac{8.5-8.2}{16}=\dfrac{24}{16}=\dfrac{3}{2}\)
\(\dfrac{11.4-11}{2-13}=\dfrac{33}{-11}=-3\)
a) \(\frac{3^2.2^4}{8.3^2}=\frac{3^2.2^4}{2^3.3^2}=2\)
b)\(\frac{84.45}{49.54}=\frac{2^2.7.3^3.5}{7^2.2.3^3}=\frac{10}{7}\)
c) \(\frac{36.10.21}{2^3.63.35}=\frac{2^3.3^3.5.7}{2^3.3^2.5.7^2}=\frac{3}{7}\)
d) \(\frac{16.29-32}{16.37+32}=\frac{16.29-16.2}{16.37+2.16}=\frac{16.\left(29-2\right)}{16.\left(37+2\right)}=\frac{27}{39}=\frac{9}{13}\)
Bài 1:
a: =-3/7
b: =-3/5
c: =1/13
d: =-1/2
Bài 2:
a: \(=\dfrac{21\cdot11}{22\cdot9}=\dfrac{1}{2}\cdot\dfrac{7}{3}=\dfrac{7}{6}\)
b: \(=\dfrac{49\cdot8}{10}=\dfrac{196}{5}\)
a)\(\frac{20}{-160}=-\frac{1}{8}\)
b)\(\frac{-24}{-72}=\frac{1}{3}\)
c)\(-\frac{270}{450}=-\frac{3}{5}\)
d)\(\frac{3.7.11}{33.14}=\frac{33.7}{33.14}=\frac{7}{14}=\frac{1}{2}\)
e)\(\frac{49+7.49}{-49}=\frac{49.\left(1+7\right)}{-49}=\frac{49.8}{-49}=-8\)
\(a,\frac{20}{-160}=\frac{-20:20}{160:20}=\frac{-1}{8}\)
\(b,\frac{-24}{-72}=\frac{-24:24}{-72:24}=\frac{-1}{-3}=\frac{1}{3}\)
\(c,\frac{-270}{450}=\frac{-270:90}{450:90}=\frac{-3}{5}\)
\(d,\frac{3.7.11}{33.14}=\frac{3.7.11}{3.11.7.2}=\frac{1}{2}\)
\(e,\frac{49+7.49}{-49}=-\frac{49.\left(7+1\right)}{49}=-8\)
Học tốt
\(\dfrac{3.17.11}{22.9}=\dfrac{17}{6}\)
\(\dfrac{84.45}{49.54}=\dfrac{10}{7}\)
\(\dfrac{4.7.22}{33.14}=\dfrac{4}{3}\)
\(\dfrac{3\cdot7\cdot11}{22\cdot9}=\dfrac{1\cdot7\cdot1}{2\cdot3}=\dfrac{7}{6}\\ \dfrac{84\cdot45}{49\cdot54}=\dfrac{12\cdot5}{7\cdot6}=\dfrac{10}{7}\\ \dfrac{4\cdot7\cdot22}{33\cdot14}=\dfrac{4\cdot1\cdot2}{3\cdot2}=\dfrac{4}{3}\)